Effect of Xuefu Zhuyu Decoction Pretreatment on Myocardium in Sepsis Rats. (9th September 2018) - Meng, Fansu; Lai, Haibiao; Luo, Zekun; Liu, Yong; Huang, Xiaoxun; Chen, Junqian; Liu, Bayi; Guo, Yingjun; Cai, Yu; Huang, Qingqing
Abstract : Xuefu Zhuyu Decoction (XFZYD), the classical recipe for promoting blood circulation by removing blood stasis, has been used in China for a long history clinically. XFZYD has been found to improve cardiac function through reducing inflammation. However, the effect of XFZYD on myocardial apoptosis remains unclear. Herein, we investigated the mechanism of XFZYD preconditioning on myocardial injury in sepsis rats. The rats were treated with XFZYD one week, followed with intraperitoneal injection of lipopolysaccharide (LPS: 10 mg/kg) to induce sepsis. Pretreatment with XFZYD could reverse the effects of LPS-induced decreased mean arterial pressure (MAP) and increased heart rate (HR). XFZYD decreased the levels of malondialdehyde (MDA), superoxide dismutase (SOD), tumor necrosis factor- α (TNF- α ), interleukin-1β (IL-1 β ), and interleukin-6 (IL-6) in serum or in heart. TUNEL staining revealed that the apoptotic index of XFZYD was significantly lower compared with the LPS group (P<0.05). Western blot results showed that the high doses of pretreatment XFZYD group can reduce the Bax expression of myocardial tissue in rats (P<0.05, P<0.01). The expression of Bcl-2 in XFZYD group was significantly higher than that in the LPS group (P<0.01), while the expression of caspase-3 in treatment group was significantly lower than that in the LPS group only after 12 h modeling (P<0.01). In addition, caspase-3 activity in rat cardiomyocytes of XFZYD-treated animals was significantly decreased. These findings suggest that pretreatment with XFZYD exerts a protective effect in the myocardium of septic rats by inhibiting myocardial cell apoptosis and antioxidation.